2011
DOI: 10.1378/chest.10-0968
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency and Reduced Lung Function in Connective Tissue-Associated Interstitial Lung Diseases

Abstract: There is a high prevalence of vitamin D deficiency in patients with ILD, particularly those with CTD-ILD, and it is associated with reduced lung function. Vitamin D may have a role in the pathogenesis of CTD-ILD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 42 publications
2
25
0
Order By: Relevance
“…Despite a rapidly growing body of scientific literature, the mechanisms underlying the potential benefit of high-dose vitamin D therapy remain uncertain. Several epidemiologic studies have shown an association between vitamin D deficiency and increased risk of respiratory infections [32] , [33] as well as an direct relationship between vitamin D and decreased lung function in patients with chronic obstructive pulmonary disease and interstitial lung disease [34] , [35] , [36] , [37] . Therapeutically, administration of 25(OH)D was associated with an increase in lung function for adult patients with asthma [38] and with improved one year survival in patients with cystic fibrosis [39] .…”
Section: Discussionmentioning
confidence: 99%
“…Despite a rapidly growing body of scientific literature, the mechanisms underlying the potential benefit of high-dose vitamin D therapy remain uncertain. Several epidemiologic studies have shown an association between vitamin D deficiency and increased risk of respiratory infections [32] , [33] as well as an direct relationship between vitamin D and decreased lung function in patients with chronic obstructive pulmonary disease and interstitial lung disease [34] , [35] , [36] , [37] . Therapeutically, administration of 25(OH)D was associated with an increase in lung function for adult patients with asthma [38] and with improved one year survival in patients with cystic fibrosis [39] .…”
Section: Discussionmentioning
confidence: 99%
“…A study on 118 patients with interstitial lung disease, including 67 patients with connective tissue disorders, revealed significantly low vitamin D levels (35). In patients with connective tissue disorders, correlations between vitamin D level and forced vital capacity and DLCO were identified.…”
Section: Methodsmentioning
confidence: 99%
“…13 Vitamin D concentration has been shown to be directly correlated with spirometry and gas exchange in subjects with interstitial lung disease. 14 Subjects with COPD who had mild vitamin D insufficiency 15 and who engaged in rehabilitation demonstrated higher functional gains when vitamin D supplementation was added to their rehabilitation regimen. 16 Furthermore, COPD subjects with severe vitamin D deficiency (< 10 ng/mL) had a significantly lower rate of COPD exacerbations with supplementation compared with those without.…”
Section: Introductionmentioning
confidence: 99%